CancellationTools: All-in-one software for administration and analysis of cancellation tasks - Dalmaijer, E; Van der Stigchel, S; Nijboer, T; Cornelissen, T; Husain, M (Springer US, 2014)
In a cancellation task, a participant is required to search for and cross out ("cancel") targets, which are usually embedded among distractor stimuli. The number of cancelled targets and their location can be used to diagnose the neglect syndrome after stroke. In addition, the organization of search provides a potentially useful way to measure executive control over multitarget search. Although many useful cancellation measures have been introduced, most fail to make their way into research studies and clinical practice due to the practical difficulty of acquiring such parameters from traditional pen-and-paper measures. Here we present new, open-source software that is freely available to all. It allows researchers and clinicians to flexibly administer computerized cancellation tasks using stimuli of their choice, and to directly analyze the data in a convenient manner. The automated analysis suite provides output that includes almost all of the currently existing measures, as well as several new ones introduced here. All tasks can be performed using either a computer mouse or a touchscreen as an input device, and an online version of the task runtime is available for tablet devices. A summary of the results is produced in a single A4-sized PDF document, including high quality data visualizations. For research purposes, batch analysis of large datasets is possible. In sum, CancellationTools allows users to employ a flexible, computerized cancellation task, which provides extensive benefits and ease of use.